GAMBARAN ADAPTABILITAS KARIR PADA SISWA SEKOLAH MENENGAH ATAS DI KARAWANG - Dian Ayu Desy Purnamasari; Herdi Herdi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
With the times, career challenges are increasingly diverse. This makes obstacles for high school students. Many high school students experience doubts in their careers after graduating from school. to deal with this problem, career adaptability is needed. The purpose of this study was to determine the description of career adaptability of high school students in Karawang. The samples in this study were 65 X grade students at high schools in Karawang. The sampling technique used was proportional simple random sampling. The data collection instrument used is the Career Futures Inventory-Revised (CFI-R) instrument by Rottinghaus totaling 28 items, then adapted into Indonesian which has gone through an adaptation process by 2 linguists with validity and reliability tests into 22 items that can be used. The results showed that in general, the career adaptability of class X high school students in Karawang was in the moderate category with the characteristics of students who had 5 aspects, namely career agency, occupational awareness, negative career outlook, support, and moderate work-life balance . Factors that can influence the formation of career adaptability are the ability of self-regulation and career exploration and work experience.